2014
DOI: 10.1074/jbc.m113.496364
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Growth Limitation of Corneal Fibrils and Their Lamellar Stacking Depend on Covalent Collagen Cross-linking by Transglutaminase-2 and Lysyl Oxidases, Respectively

Abstract: Background: Mechanisms of growth limitation and lamellar stacking of collagen fibrils in cornea remain elusive. Results: Covalent collagen cross-links are formed by catalysis involving both lysyl oxidases and tissue transglutaminase-2. Conclusion: Aldehyde-derived and isopeptide cross-linking of collagen determine lamellar stacking and lateral fibril growth, respectively. Significance: Two types of covalent collagen cross-linking are indispensable for correct corneal morphogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…Three-dimensional tissue constructs from chick corneal fibroblasts were manipulated with BAPN and transglutaminase inhibitor. Transglutaminase inhibition again had a similar effect as the above described collagen V absence: collagen fibrils showed broadened diameter spectra and random shapes (20). Interestingly, BAPN treatment had no effect on fibril shape in contrast to the present study.…”
Section: Targetcontrasting
confidence: 53%
See 2 more Smart Citations
“…Three-dimensional tissue constructs from chick corneal fibroblasts were manipulated with BAPN and transglutaminase inhibitor. Transglutaminase inhibition again had a similar effect as the above described collagen V absence: collagen fibrils showed broadened diameter spectra and random shapes (20). Interestingly, BAPN treatment had no effect on fibril shape in contrast to the present study.…”
Section: Targetcontrasting
confidence: 53%
“…A recent study focusing on corneal development investigated the effects of LOX and transglutaminase induced cross-linking on cornea collagen fibrils (20). Three-dimensional tissue constructs from chick corneal fibroblasts were manipulated with BAPN and transglutaminase inhibitor.…”
Section: Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, previous evidence supported a function of TG in stabilizing and cross‐linking ECM proteins; however, whether TG activity was critical in collagen fiber assembly in vivo was not established. Our current studies show that the absence of SPARC was associated with increased TG activity and smaller collagen fibrils, consistent with results by Wang and colleagues that showed inhibition of TG activity increased collagen fibril diameter in ECM assembled by cornea fibroblasts. Assembly of an insoluble fibronectin network has been shown to play a critical role in collagen ECM assembly in cultured cells .…”
Section: Discussionmentioning
confidence: 99%
“…In corneal morphogenesis it recently has been reported that two types of covalent collagen cross-links formed by catalysis involving LOXs and TGM2 are essential. 48 The TGM2 mRNA and protein have been shown to be downreg- ulated in pterygium, indicating that this decreased activity could facilitate the migration of abnormal pterygium tissue toward the central cornea. 42 Among other eye diseases related to the elastic component, ectopia lentis and myopia are frequently observed ocular manifestations of Marfan syndrome, which involves common defects in FBN1 microfibrils causing a wide spectrum of disorders.…”
Section: Discussionmentioning
confidence: 98%